“GEBYAR CERIA PINAM” as Complementary Therapy to Increase Toddlers’ Appetite: Terapi Komplementer “GEBYAR CERIA PINAM” untuk Meningkatkan Nafsu Makan Balita - Shinta Novelia; Vindi Akati; Yeni Andriani; Evi Puspita Sari; Siti Khotijah; Cynthia Febriani; Raden Nova Nurutami; Puji Sutama Putri; Herlinah (KHD Production, 2025)
The nutritional needs of children aged 24 - 60 months tend to increase because children are in a period of growth accompanied by busy activities. Feeding children at this age requires sufficient patience. If the amount of activity of toddlers is not balanced with nutritious intake, it will affect the health and ability of toddlers to reach their developmental stages. The aim of this community activity is to provide mothers with creativity in making healthy creative snacks and regarding non-pharmacological management to overcome children's lack of appetite. This community service method uses lecture, discussion and demonstration methods that focus on mothers who have children aged 24 - 60 months. This activity can provide insight into counseling and demonstrations regarding feeding babies and children and complementary care